Disseminating effective use of mapping techniques in integral calculus / Nor Hazizah Julaihi, Voon Li Li and Tang Howe Eng - Julaihi, Nor Hazizah; Voon, Li Li; Tang, Howe Eng (ACRULeT, Faculty of Education & UiTM Press, 2013)
Integral Calculus has always been an issue to first year Engineering students in their Calculus courses in higher learning institutions. This paper studied mapping techniques in learning Integral Calculus. Fifty-three randomly selected first year Engineering respondents were asked to sit for a pre-test, then exposed to a treatment and finally sat for a post-test. The findings showed that there was a signifi cantly higher mean of post-test scores as compared to the mean of pre-test scores after the application of Integral Maps in their learning. The fi dings indicated that the mapping techniques had a positive effect on the respondents. The respondents were fascinated with the applied bright colours in the maps. They were also fast in working out solutions as they exploited the layering design of the maps. All of the respondents would use or recommend the maps to their friends. The fi ndings indicate that mapping techniques have potential for applications in the teaching and learning of Integral Calculus.